Adropin Predicts Chronic Kidney Disease in Type 2 Diabetes Mellitus Patients with Chronic Heart Failure - Berezina, T. A.; Obradovic, Z.; Boxhammer, E.; Berezin, A. A.; Lichtenauer, M.; Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2023)
Abstract: Adropin is a multifunctional secreted protein, which is involved in the metabolic modulation of the heart‐brain‐kidney axis in heart failure (HF). The aim of the study was to detect the plausible predictive value of serum levels of adropin for chronic kidney disease (CKD) grades 1–3 in type 2 diabetes mellitus (T2DM) patients with chronic HF. We enrolled 417 T2DM individuals with chronic HF and subdivided them into two groups depending on the presence of CKD. The control group was composed of 25 healthy individuals and 30 T2DM patients without HF and CKD. All eligible patients underwent an ultrasound examination. Adropin was detected by ELISA in blood samples at the study baseline. We found that adropin levels in T2DM patients without HF and CKD were significantly lower than in healthy volunteers, but they were higher than in T2DM patients with known HF. The optimal cut‐off point for adropin levels was 2.3 ng/mL (area under the curve [AUC] = 0.86; 95% CI = 0.78–0.95; sensitivity = 81.3%, specificity = 77.4%). The multivariate logistic regression adjusted for albuminuria/proteinuria showed that serum levels of adropin <2.30 ng/mL (OR = 1.55; p = 0.001) independently predicted CKD. Conclusions: Low levels of adropin in T2DM patients with chronic CH seem to be an independent predictor of CKD at stages 1–3.
Keywords: type 2 diabetes mellitus; heart failure; chronic kidney disease; adropin; biomarkers; prediction